Penentuan Batas Transfer Daya Listrik Dengan Meminimalkan Pembangkitan Daya Pada Pembangkit Subsistem Studi Kasus : Subsistem 275 KV Sumbegsel - Sumbagteng PT PLN (PERSERO) P3BS - Gesit Septiadi; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In the single line of electric power flow, there are a lot of things to be aware such as the capacity of system installation equipment and also the equipment will be utilized. This analysis aims to measure the extent of power transfer between subsystems Sumbagsel to Sumbagteng can be maximized by using extra high voltage of overhead conductor 275 kV. This study without breaking the boundaries of operation of the existing rule. The calculation in this analysis using software assisted with Newton Raphson power flow method to calculate several possible scenarios. The amount of maximum power transfer subsystem Sumbagsel towards Sumbagteng is 557,6 MW without operating compensator and the amount of power transfer by operating the compensator is 586 MW.Keywords: Power flow, Newton Raphson Method, 275 kV Sumatera system